2018
DOI: 10.26444/aaem/75801
|View full text |Cite
|
Sign up to set email alerts
|

Stress factors vs. job satisfaction among nursing staff in the Pomeranian Province (Poland) and the Vilnius Region (Lithuania)

Abstract: Introduction. In the opinion of many researchers, nursing staff are exposed to an exceptionally high level of occupational stress. The problem of stress in the working environment of the nursing staff becomes more and more important in the context of increasing staff shortages and insufficient support from colleagues and employers. The aim of this study was to analyse stress factors indicated by the nursing staff in Poland and Lithuania, and to assess their job satisfaction. Materials and method. Two standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
2
10
0
3
Order By: Relevance
“…4). confirm that high job dissatisfaction among the nursing staff is connected with bad internal organization of the workplace, conflicts with supervisors, and a lack of understanding between nurses and their supervisors [22]. Gurková, et al [12] conducted an international cross-sectional study aimed at subjective wellbeing of nurses (n=1055) utilizing PWI-A scale and identified the score of satisfaction with life at 60-70% maximum of 100% scale which corresponded with our findings.…”
Section: Resultssupporting
confidence: 88%
“…4). confirm that high job dissatisfaction among the nursing staff is connected with bad internal organization of the workplace, conflicts with supervisors, and a lack of understanding between nurses and their supervisors [22]. Gurková, et al [12] conducted an international cross-sectional study aimed at subjective wellbeing of nurses (n=1055) utilizing PWI-A scale and identified the score of satisfaction with life at 60-70% maximum of 100% scale which corresponded with our findings.…”
Section: Resultssupporting
confidence: 88%
“…The nursing profession is considered to be a stressful and emotionally demanding profession; nurses in their everyday practice are dealing with various stressors, such as critical situations, workload, grief, death [ 1 ], nurses–physician collaboration and conflicts and uncertainty about the effectiveness of the provided care [ 2 ]. Moreover, the COVID-19 pandemic exposes nurses to additional stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have dealt with the evaluation of the satisfaction of the nursing staff and the factors that affect it. Excessive workload, demanding cyclical working shifts, non-assignment of roles, authoritarian management, poor opportunities for development, lack of solidarity with colleagues, the need for harmonious cooperation between many and different specialties of health professionals, the frequent contact of the health professional with people in need, but also the frequent exposure to the death of patients, compose particularly stressful and adverse working conditions, which affect the satisfaction of the nursing staff [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%